The effect of sodium ascorbate application and intracoronal bleaching on the shear bond strength of composite resin - Rama Insan Kusuma Wijaya; Tunjung Nugraheni; Tri Endra Untara (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
An increase in the frequency of 35% hydrogen peroxide (HP) application during intracoronal bleaching leads to a higher accumulation of free radical residues, which can negatively affect the bonding of composite resin. The removal of these free radicals can be facilitated by the application of 35% sodium ascorbate (SA) combined with 0.4% surfactant. An additional frequency of SA application is required to counteract the increased free radical residues. This study aimed to evaluate the effect of the frequency of 35% SA combined with 0.4% surfactant and different intracoronal bleaching frequencies on the shear bond strength of composite resin. Forty-eight premolar teeth were divided into two main groups of 24 specimens each. Group I received two applications of 0.01 mL HP 35%, while Group II received three applications. After each bleaching session, the specimens were stored in a closed tube for five days per session, then washed and dried. Each group was further divided into three subgroups. Subgroup A was left untreated for seven days; Subgroup B received two applications of 35% sodium ascorbate combined with 0.4% surfactant; and Subgroup C received three applications. All specimens were restored with composite resin and immersed in pH 7 artificial saliva in an incubator for seven days. Shear bond strength was tested using a Universal Testing Machine at a crosshead speed of 0.5 mm/min. Two-way ANOVA revealed a significant effect of sodium ascorbate application frequency and different intracoronal bleaching frequencies on composite resin shear bond strength (p < 0.01). The results indicate that the shear bond strength of composite resin subjected to three applications of 35% sodium ascorbate combined with 0.4% surfactant is statistically comparable to those obtained with two applications of the same formulation.